CHI '06 Extended Abstracts on Human Factors in Computing Systems 2006
DOI: 10.1145/1125451.1125549
|View full text |Cite
|
Sign up to set email alerts
|

Online health communities

Abstract: Online health communities provide a means for patients and their families to learn about an illness, seek and offer support, and connect with others in similar circumstances. They are supported by a variety of technologies (e.g., email lists, forums, chat rooms) and are hosted by patients, advocacy groups, medical organizations, and corporations. They raise difficult design challenges because of the wide variability of members' medical expertise, the severity of problems due to misinformation, and the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 2 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…This shift is attributed mostly to changes in the healthcare system (including decreased access to healthcare professionals and higher costs of healthcare) and increased technological literacy in the patient population. 1 While PAT may not contain scientifically accurate or systematic data, it comprises rich descriptions of hundreds of patients’ experiences over a wide range of conditions, in real time. Already, projects such as Google Flu 2 and HealthMap 3 have shown that PAT is a reliable data source for tracking disease trends; moreover, novel insights into co-morbidities and drug-treatment effects have been discovered on sites like CureTogether 4 and PatientsLikeMe.…”
Section: Objectivementioning
confidence: 99%
“…This shift is attributed mostly to changes in the healthcare system (including decreased access to healthcare professionals and higher costs of healthcare) and increased technological literacy in the patient population. 1 While PAT may not contain scientifically accurate or systematic data, it comprises rich descriptions of hundreds of patients’ experiences over a wide range of conditions, in real time. Already, projects such as Google Flu 2 and HealthMap 3 have shown that PAT is a reliable data source for tracking disease trends; moreover, novel insights into co-morbidities and drug-treatment effects have been discovered on sites like CureTogether 4 and PatientsLikeMe.…”
Section: Objectivementioning
confidence: 99%
“…Online health communities serve as a common learning environment that enhances social interactions and sharing of experiences which facilitates learning. However, online health communities raise challenges because of the differences of members, health literacy, and medical knowledge (Neal et al, 2007).…”
Section: Social Cognitive Theory and Online Learningmentioning
confidence: 99%
“…Health “communities” can develop online, established independent of time and geographical space (Douglas et al, 2008). People can connect with others in similar circumstances (Neal et al, 2007; Broom & Tovey, 2008; Hinton, Kurinczuk, & Ziebland, 2010) and can learn to better manage long-term problems or conditions. Posting on YouTube is likely to have different rewards for the posters, such as gaining credibility, becoming a spokesperson for a stigmatized group, and/or attaining hero status (Fixsen, 2015).…”
Section: Introductionmentioning
confidence: 99%